FEM modelling of magnetoelectric coupling in (2-2)LSMO/ P(VDF-TrFE) polymer composite. Issue 1 (1st July 2022) - Koner, S; Sumit,; Shukla, R; Majumder, S K; Satapathy, S
Abstract: Strain mediated magnetoelectric (ME) coupling effect has been investigated in bilayer structure of LSMO/P (VDF-TrFE) nanocomposite in the transverse ME mode. In the transverse mode, Finite Element Method (FEM) based small signal analysis has been performed by the COMSOL Multiphysics 6.0 software. La0.7 Sr0.3 MnO3 (LSMO)/P (VDF-TrFE) nanocomposite (2-2) has been prepared by gluing LSMO pellet with P(VDF-TrFE) polymer film. This bilayer structure shows multiferroic property at room temperature. Simulated FEM modelverifies the magneto-strictive property of LSMO layer and explained the experimental results.Experimental and simulated ME coupling coefficient are found to be very close to each other.